Nilai Pendidikan Agama Hindu Dalam Pementasan Tari Sang Hyang Dedari - Sumertayasa, Kadek Yogi; Nerawati, Ni Gusti Ayu Agung; Ariasa Giri, I Made; Setyaningsih, Farida; Suarnaya, I Putu (Jayapangus Press, 2023)
Balinese life cannot be separated from art, because it is attached to religion. This is evident in the performance of dance which has a function closely related to Hindu religious ceremonies. One of these sacred dances is the Sang Hyang Dedari dance. The purpose of this study is to describe the value of Hindu religious education through the Sang Hyang Dedari Dance Performance. The research method used is qualitative research. The results showed that the educational values of Hinduism contained in the staging of the Sang Hyang Dedari Dance were the values of tattwa/philosophical education, the values of ethics/sincere education of sincerity, the values of ceremonial or ceremonial education, the values of love, and the values of peace. The community believes that every performance of the Sang Hyang Dedari Dance is able to provide welfare and protect residents from danger.